2023
DOI: 10.3399/bjgp.2022.0475
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delays for breathlessness in primary care: a qualitative study to investigate current care and inform future pathways

Abstract: Background: Evidence to understand the delays to diagnosis for patients presenting with breathlessness is lacking. Aim: To explore current care through the experiences of adults presenting with chronic breathlessness awaiting a diagnosis and primary care clinicians. Design and Setting: Qualitative study with adults presenting with chronic breathlessness, and clinicians in primary care. Methods: Semi-structured interviews were conducted with patients and clinicians. Participants were recruited from a feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…As such, it has been associated with poor quality of life and survival, usually leading the patient to seek healthcare at an ER or with their FD [ 7 ]. Therefore, some patients end up delaying seeking medical help because of neglecting their symptoms, health illiteracy, or lack of timely access to healthcare [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, it has been associated with poor quality of life and survival, usually leading the patient to seek healthcare at an ER or with their FD [ 7 ]. Therefore, some patients end up delaying seeking medical help because of neglecting their symptoms, health illiteracy, or lack of timely access to healthcare [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings were similar in a survey of over 4000 German adults (40% with at least one chronic condition) [ 44 ] which identified that preferred sources of health information were health professionals (general practitioners (72.1%), specialists (39.5%), and pharmacists (31.6%)) rather than the internet (31.5%), although reasons for these preferences were not reported. Subsequent to the conduct of these studies, the coronavirus disease 2019 (COVID-19) pandemic disrupted an already unpredictable diagnostic pathway for people experiencing breathlessness [ 45 , 46 ], which prompted an explosion of online health information and misinformation [ 47 ], a shift to remote delivery of healthcare [ 48 ], and the emergence of persistent breathlessness after COVID-19 infection [ 49 ]. Research into the impact of virtual information sources on breathlessness representations in this rapidly changing environment is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In their qualitative study of clinician and commissioner stakeholders in England, Doe et al, report barriers to providing spirometry in primary care and opportunities for improvement. 11 Before the COVID-19 pandemic, challenges included a lack of clear and consistent funding for providing spirometry services, variation in the quality of spirometry performance and interpretation, and an imperfect accreditation process for achieving competency in spirometry. 11 With spirometry halted during the pandemic, a huge backlog of cases increased pressure on existing services, adding to pre-pandemic challenges.…”
Section: Importancementioning
confidence: 99%
“…11 Before the COVID-19 pandemic, challenges included a lack of clear and consistent funding for providing spirometry services, variation in the quality of spirometry performance and interpretation, and an imperfect accreditation process for achieving competency in spirometry. 11 With spirometry halted during the pandemic, a huge backlog of cases increased pressure on existing services, adding to pre-pandemic challenges. 12 Some services never re-started.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation